Defect-rich bimetallic yolk–shell metal-cyanide frameworks as efficient electrocatalysts for oxygen evolution reactions. Issue 4 (17th December 2020) - Feng, Yongqiang; Dong, Peipei; Cao, Liyun; Wang, Xiao; Wang, Jia; Wang, Hai; Feng, Weihang; Chen, Junsheng; Feng, Liangliang; He, Chaozheng; Huang, Jianfeng
Abstract : A defect-rich yolk–shell Co–Fe Prussian-blue analogue was fabricated using a reduction-induced dissolution–recrystallization strategy, which exhibited enhanced OER performance in an alkaline medium. Abstract : The rational design and construction of noble-metal-free electrocatalysts with high activity and robust durability for oxygen evolution reactions (OERs) have aroused immense interest in the past decades, but challenges remain. Herein, a reduction-induced dissolution–recrystallization (RIDR) strategy was developed to fabricate a defect-rich yolk–shell Prussian-blue analogue (YS-PBA) by a solvothermal process in isopropyl alcohol (IPA) in the presence of polyvinylpyrrolidone (PVP). The experimental result indicated that the defect-rich YS-PBA was formed via phase transformation from Co3 [Fe III (CN)6 ]2 to Co2 Fe II (CN)6 induced by the reduction potential of the IPA-PVP couple. The newly synthesized YS-PBA exhibited outstanding OER performance with a low overpotential of 293 mV to deliver a current density of 10 mA cm −2 and long-term durability (120 h) in alkaline media. Both experimental and density functional theory (DFT) results unveiled that the defects formed in YS-PBA cause a dramatic positive effect on the improvement of the OER activity.